2013
DOI: 10.1002/lary.24209
|View full text |Cite
|
Sign up to set email alerts
|

Effects of asymmetric superior laryngeal nerve stimulation on glottic posture, acoustics, vibration

Abstract: Objectives Evaluate the effects of asymmetric superior laryngeal nerve stimulation on the vibratory phase, laryngeal posture, and acoustics. Study Design Basic science study using an in vivo canine model. Methods The superior laryngeal nerves were symmetrically and asymmetrically stimulated over eight activation levels to mimic laryngeal asymmetries representing various levels of superior laryngeal nerve paresis and paralysis conditions. Glottal posture change, vocal fold speed, and vibration of these 64 d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
53
0
7

Year Published

2014
2014
2017
2017

Publication Types

Select...
8

Relationship

7
1

Authors

Journals

citations
Cited by 38 publications
(65 citation statements)
references
References 24 publications
5
53
0
7
Order By: Relevance
“…As mentioned before, the threshold and maximal activation levels for each nerve was rechecked at the end of the stimulation run and remained unchanged. These findings are also consistent with the laryngeal behavior in previous reports (Chhetri et al, 2012(Chhetri et al, , 2013 where the number of concurrently and independently activated muscles was smaller.…”
Section: Data Presentation and Interpretationsupporting
confidence: 92%
See 1 more Smart Citation
“…As mentioned before, the threshold and maximal activation levels for each nerve was rechecked at the end of the stimulation run and remained unchanged. These findings are also consistent with the laryngeal behavior in previous reports (Chhetri et al, 2012(Chhetri et al, , 2013 where the number of concurrently and independently activated muscles was smaller.…”
Section: Data Presentation and Interpretationsupporting
confidence: 92%
“…In addition, separately controlling the two laryngeal adductors appears critical to achieving the high F0 values and register jumps. The F0 range achieved in this study by separately activating the TA and LCA/IA nerve branches was at least twice that we and others have previously encountered in an in vivo canine model of phonation where all adductors were activated together by stimulating the RLN (Chhetri et al, 2012(Chhetri et al, , 2013. This would support the notion that separate control of membranous and cartilaginous glottis could significantly increase the variety of phonation types (Herbst et al, 2011).…”
Section: Discussionsupporting
confidence: 81%
“…It is important to quantify the affect of using a suture to adduct the folds because it has been shown that different excitation levels of laryngeal muscle excitation (i.e. different magnitudes of pre-stress) can change the dynamics and the acoustic characteristics of the folds (Chhetri et al [33]). The current study also did not account for the viscoelastic response of the vocal fold tissue, and the resultant measures of the Young's modulus of the tissue may be overestimated.…”
Section: Discussionmentioning
confidence: 99%
“…The larynx was exposed and exteriorized in the neck as previously described. 4,5 Briefly, a vertical midline skin incision was made to provide wide exposure of the laryngotracheal framework. Tracheostomy tube was placed and the oral endotracheal tube was removed.…”
Section: Methodsmentioning
confidence: 99%
“…4,5 The thyroarytenoid (TA) forms the physical bulk of the glottis and upon contraction causes shortening, medial bulging, and adduction of the membranous vocal folds and imparts stiffness to the body layer. The lateral cricoarytenoid (LCA) muscle adducts the vocal fold at its attachment to the vocal process, achieving posterior glottal closure.…”
Section: Introductionmentioning
confidence: 99%